PERTUMBUHAN DAN PRODUKTIVITAS KELOR (Moringa oleifera) PERIODE VEGETATIF AWAL DENGAN PEMUPUKAN SUMBER P YANG BERBEDA PADA TANAH ULTISOL - Simel Sowmen; Rusdiamansyah Rusdiamansyah; Siti Zainab; Mari Santi (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
Greenhouse study was conducted to investigate the effects of phosporous fertilizer on the growth and production of Moringa oleifera in ultisol. The experimental design was Completely Randomized Design (CRD), treatments which include 0 kg/ha, 100 kg/ha SP36, 200 kg/ha SP36, 300 kg/ha SP36, 100 kg/ha Rock Phospat (RP), 200 kg/ha RP, and 300 kg/ha RP, in five replicates. The result showed there wasn’t signicantly differences (P>0.05) of all phosporous fertilizer treatment to growth and production of moringa in early vegetative periode. Keywords: plants growth, Moringa oleifera, phosporous fertilizer